2023
DOI: 10.1097/md.0000000000034649
|View full text |Cite
|
Sign up to set email alerts
|

Serum sclerostin level is positively associated with endothelial dysfunction measured by digital thermal monitoring in patients with type 2 diabetes: A prospective cross-sectional study

Bang-Gee Hsu,
Du-An Wu,
Hsin-Yu Yang
et al.

Abstract: Sclerostin and dickkopf-1 (DKK1), extracellular inhibitors of the canonical Wnt/β-catenin signaling pathway, have been associated with vascular aging and atherosclerosis. This study aimed to assess the correlation of sclerostin and DKK1 concentrations with endothelial function measured using vascular reactivity index (VRI) in patients with type 2 diabetes mellitus (T2DM). Fasting blood samples were collected from 100 patients with T2DM. Endothelial function and VRI were measured using digital thermal monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Evidence indicates that vascular ED begins early in arteriosclerosis and is observable during early glucose intolerance in patients with T2DM [ 5 ]. Additionally, DM contributes to ED progression [ 5 , 11 ], and a study also reported that some classic hypoglycemic agents may ameliorate both ED and hyperglycemia [ 22 ]. Earlier studies indicate that chronic hyperglycemia induces ED through varied pathways: heightened reactive oxygen species (ROS) from hyperglycemia, elevated transforming growth factor-β and plasminogen activator inhibitor-1, and diminished NO availability impacting both macrovascular and microvascular function [ 1 ] As expected, our study found elevated fasting glucose and HbA1C level are inversely related to vascular reactivity in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence indicates that vascular ED begins early in arteriosclerosis and is observable during early glucose intolerance in patients with T2DM [ 5 ]. Additionally, DM contributes to ED progression [ 5 , 11 ], and a study also reported that some classic hypoglycemic agents may ameliorate both ED and hyperglycemia [ 22 ]. Earlier studies indicate that chronic hyperglycemia induces ED through varied pathways: heightened reactive oxygen species (ROS) from hyperglycemia, elevated transforming growth factor-β and plasminogen activator inhibitor-1, and diminished NO availability impacting both macrovascular and microvascular function [ 1 ] As expected, our study found elevated fasting glucose and HbA1C level are inversely related to vascular reactivity in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Waist circumference was determined by measuring the mid-point between the lower ribs and the hip bones, with the participants placing their hands on their hips. The body mass index (BMI) was computed by dividing the weight in kilograms by the square of the height in meters [ 11 , 12 ]. Blood pressure was measured in the morning after a 10 min seated rest using standard mercury sphygmomanometers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations